VERBA EMOSI STATIF DALAM BAHASA MELAYU ASAHAN - Mulyadi Mulyadi (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2010)
This research proposes a new perspective in analyzing emotion stative verbs, i.e. starting from meaning to form, by presenting the evidence from the Asahan Malay language. The data was collected by using questionnaire, observation, interview, and intuition methods. The analysis concerns the mapping of semantic components of emotion stative verbs, which is used to determine their subcategory. For the analysis, the semantic primes of the Natural Semantic Metalanguage theory are applied. The study shows that emotion stative verbs of Asahan Malay are characterized by the component ‘X felt something not because X wanted this’. In accordance with the types of events, emotion stative verbs are divided into four subcategories: (1) ‘something bad has happened’ (“sodih-like”), (2) ‘something bad can/will happen’ (“takut-like”), (3) ‘people can know something bad about me’ (“malu-like”), and (4) ‘I don’t think that things like this can/will happen’ (“heran-like”).